From Performance to Literature and Cinema: Adivasi Art and Activism, with a Focus on Eastern India - Raphaël Rousseleau (South Asia Multidisciplinary Academic Journal)
Activist art is a rather recent development within contemporary art, articulating reflections on artistic expression, art commodification, and political criticism. When it comes to Adivasi arts, however, one tends to think of dances or of Gond and Warli paintings of trees and animals. This article seeks to explore the confluence between Adivasi art and activism, while addressing what could be referred to as the “triple bond” of Adivasi artists. Contemporary Indian artists already face a sort of double bond in the sense that they tend to be recognized either as “contemporary artists” or as “Indian artists.” The position of Adivasi artists is further complicated (Rousseleau 2017) by the fact that they belong to an economically disadvantaged cultural minority within India (Scheduled Tribes). Inasmuch as they tend to be labeled according to their origins, Adivasi artists find themselves caught between stigma, an ascribed identity and their self-conception, thus facing three key issues: moral judgement, folklorization and appropriation, and identity conflicts. This article portrays the complex situation of contemporary Adivasi artists, drawing both on historic landmarks in developments in the way Adivasi arts—that is dancing and singing, theater, painting, literature, fiction and non-fiction films—are received, and on artists’ assertion of cultural and political identity.